Pros and Cons of Vitamin K Antagonists and Non–Vitamin K Antagonist Oral Anticoagulants - Riva, Nicoletta; Ageno, Walter (Seminars in Thrombosis and Hemostasis, 2015)
Anticoagulant treatment can be currently instituted with two different classes of drugs: the vitamin K antagonists (VKAs) and the newer, “novel” or non–vitamin K antagonist oral anticoagulant drugs (NOACs). The NOACs have several practical advantages over VKAs, such as the rapid onset/offset of action, the lower potential for food and drug interactions, and the predictable anticoagulant response. However, the VKAs currently have a broader spectrum of indications, a standardized monitoring test, and established reversal strategies. The NOACs emerged as alternative options for the prevention and treatment of venous thromboembolism and for the prevention of stroke and systemic embolism in patients with nonvalvular atrial fibrillation. Nevertheless, there remain some populations for whom the VKAs remain the most appropriate anticoagulant drug. This article discusses the advantages and disadvantages of VKAs and NOACs.
Keywords: vitamin K antagonist; direct thrombin inhibitor; direct factor Xa inhibitor